PENGARUH PENGGUNAAN METODE PQ4R (PREVIEW, QUESTION, READ, REFLECT, RECITE, REFIEW) TEHADAP HASIL BELAJAR EKONOMI SISWA KELAS X SEMESTER GENAP SMA NEGERI 1 PUNGGUR - Nindy Rahayu; Tiara Anggia Dewi (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
PQ4R learning method is one part of elaboration strategy. This strategy is used to help students remember what they read. P stands for preview (quick reading glance), Q is question (asks), and 4R stands for read (reads), reflect (reflections), recite (frequently asked questions), and review (repeats thoroughly). This strategy is used to assist students in the process of teaching and learning in the classroom which is carried out with the activities of reading books. While the learning outcomes is an interaction that has been achieved accepting a settlement in the form of cognitive, affective, and psychomotor are realized in the form of numeric values in the KKM 75.General pattern of learning activity is the interaction between teachers and learners with the intermediary material in the learning activities chosen by the teacher models will affect the activities of learners are manifold. In this case use the learning model will determine the quality of learning outcomes. In this learning process there must be constraints faced, one is selecting the right model for the learning process.